Development of a new method for stone coal converting into a liquid high-temperature heat carrier based on energy factors - Glikina, Irene; Zubtsov, Yevhen (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is coal processing with synthesis gas as the target product. The experimental technology employs a reactor with a liquid high-temperature heat carrier. The technological advancement allows ecological and safe transformation of hard raw material – hard coal. Hard, brown, and salty coal contains quite a lot of mineral impurities. Thermodynamic analysis of chemical transformations of coal according to its content has been carried out. The analysis was performed under the conditions of the new technology. The technology makes it possible to work simultaneously with solid, liquid, and gas structures. The main technological parameters are considered to be atmospheric pressure, temperature from 1073 to 1373 K, composition and height of the heat carrier in the reactor. The optimal temperature conditions for the process in the melt were revealed. The research was related to the characteristics and properties of liquid high-temperature heat carrier. Two types of laboratory reactors were studied. The composition and volume of the liquid heat carrier contributes to a stable and balanced progress of the target process. The proposed scheme of a reactor with a liquid high-temperature heat carrier for the coal gasification process allows for an environmentally friendly process. The designed scheme contains three zones of the process: conversion, oxidation, and post-oxidation. The reactor scheme is quite simple in structure. The technology in liquid high-temperature heat carrier involves one heat carrier for three reactor zones. The target product of processing is synthesis gas. Synthesis gas can be used directly as a target product with hydrogen being an alternative energy source. Synthesis gas as a raw material can be used to obtain hydrocarbons, separate use of substances for various industries and transformation into various compounds of organic and inorganic synthesis